Neonatal rhinorrhea, heart rate variability, and childhood exercise-induced wheeze - Sophie Berger, MD; Nicolò Pini, PhD; Maristella Lucchini, PhD; J. David Nugent, MA; Luis Acosta, MD; Jyoti Angal, MPH; Virginia A. Rauh, ScD; Amy J. Elliott, PhD; Michael M. Myers, PhD; William P. Fifer, PhD; Matthew S. Perzanowski, PhD (Journal of Allergy and Clinical Immunology: Global, 2023)
Background: There is increasing evidence linking infant rhinorrhea to school-age exercise-induced wheeze (EIW) via a parasympathetic nervous system pathway. The ratio of the root mean square of successive differences in heart beats (RMSSD) measured in quiet sleep versus active sleep (RMSSDQS:AS) is a novel biomarker in asthma. Objective: We tested the hypotheses that (1) neonatal rhinorrhea predicts childhood EIW independent of other neonatal respiratory symptoms, (2) neonatal RMSSDQS:AS predicts childhood EIW, and (3) RMSSDQS:AS mediates the association between neonatal rhinorrhea and childhood EIW. Methods: Participants from the Safe Passage/Environmental Influences on Child Health Outcomes (PASS/ECHO) prospective birth cohort had heart rate variability extracted from electrocardiogram traces acquired in the first month of life. Parents reported on rhinorrhea in their child at age 1 month and on EIW in their child at ages 4 to 11 years. Results: In models (N = 831) adjusted for potential confounders and covariates, including neonatal wheeze, cough and fever, neonatal rhinorrhea–predicted childhood EIW (relative risk [RR] = 2.22; P = .040), specifically, among females (RR = 3.38; P = .018) but not males (RR = 1.39; P = .61). Among participants contributing data in both active and quiet sleep (n = 231), RMSSDQS:AS predicted EIW (RR = 2.36; P = .003) and mediated the effect estimate of neonatal rhinorrhea predicting EIW among females. Half of the females with a higher RMSSDQS:AS and neonatal rhinorrhea (n = 5 of 10) developed EIW as compared with 1.8% of the other females (n = 2 of 109) (P < .001). Conclusions: Our findings support dysregulation of the parasympathetic nervous system in infancy as one of the possible underlying mechanisms for the development of EIW later in childhood among females, which could aid in the development of future interventions.